Identifikasi Peninggalan Bersejarah Minak Braja Selebah Sebagai Sumber Belajar IPS - Anisa Mayzar; Karsiwan, Karsiwan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This research aims to investigate the historical heritage of Minak Braja Selebah as a social studies learning resource. By using a qualitative descriptive method the author carried out several techniques to collect data, namely by using interview methods, participant observation and literature study. From the results of research conducted by the author in the villages of Braja Luhur, Braja Mulya and Jepara Village, the results showed that Minak Braja Selebah is the oldest tribe from the formation of Braja Selebah sub-district and Way Jepara sub-district, which was first centered in the Braja Selebah area or more precisely, the government was centered in Braja Village. sublime. During the observations, several historical relics were obtained which local residents believe to be evidence of the reign of Minak Braja Selebah. Evidence of heritage found is; manuscripts, ceramic jars, ceramic plates, and tombs made from a collection of stones. The learning resources used in social studies learning cover various things in social life in society, one of which is ethnopedagogy, which views local knowledge or wisdom as a source of innovation and skills that can be used for the welfare of society. By using ethnopedagogy, social studies learning can better implement social values ​​in society.